PERSEPSI PESERTA DIDIK SMA NEGERI 1 GUNUNG MERIAH TENTANG KETERKAITAN PEMAHAMAN NILAI-NILAI KRISTIANI TERHADAP PERILAKU PENYIMPANGAN PADA MATERI SISTEM REPRODUKSI MANUSIA - Putri, Ananda; Ardi (Universitas Cokroaminoto Palopo, 2024)
The aim of this research is to reveal the relationship between understanding Christian values ​​and deviant behavior in the human reproductive system. The sample in this study was class 11 science, totaling 28 people. The instrument used was a questionnaire with data analysis using descriptive percentages. The results of research on the relationship between understanding Christian values ​​and deviant behavior in the human reproductive system show an average of 75.4% in the good category.